Effect of ozone on Listeria monocytogenes in Atlantic salmon during storage - Volkute, Laura; Zvirdauskiene, Renata; Kazernaviciute, Rita; Tichonovas, Martynas; Sipailiene, Ausra (2017)
Ozone is a strong oxidant that also possesses antimicrobial properties and deodorizing effects, and thus offers many advantages in the food industry. The objective of this research was to investigate the influence of gaseous ozone treatments on the microbial and lipid oxidation of Atlantic salmon fillets inoculated with Listeria monocytogenes during refrigerated storage at 1 ᵒC for 5 days. It was found that application of ozone reduced the total count of bacteria (TCB) and L. monocytogenes number in salmon fillet during the storage. However, the influence of higher dose (3.0 mg L-1) of ozone on the total number of bacteria was the same as compared to lower dose (1.3 mg L-1) of ozone. The thiobarbituric acid reactive substances (TBARS) and the induction period assays were used to monitor oxidation in salmon fillet samples. TBARS assay indicated that no significant changes occurred in the level of oxidation of salmon fillet during ozonation at both ozone concentrations. Results of the present study showed initial of TCB and L. monocytogenes can be considerably reduced by (1.3 mg L-1) dose of gaseous ozone treatment without causing significant increases in lipid oxidation levels in salmon fillets. Although extension in refrigerated shelf-life was not observed because further research is still needed to evaluate the changes in nutritional and sensorial properties of salmon fillets.